Activated myofibroblasts promote cardiac hypertrophy and systolic dysfunction independently of cardiac fibrosis in experimental autoimmune myocarditis. (14th October 2021) - Tkacz, K; Jazwa-Kusior, A; Rolski, F; Dzialo, E; Weglarczyk, K; Czepiel, M; Siedlar, M; Kania, G; Blyszczuk, P
Abstract: Background/Introduction: Heart-specific inflammation – myocarditis is a common cause dilated cardiomyopathy which is characterized by pathological tissue remodeling, ventricular stiffening, cardiomyopathy and heart failure. In experimental autoimmune myocarditis (EAM) susceptible mice immunized with alpha myosin heavy chain (αMyHC) and complete Freund's adjuvant (CFA) develop acute myocarditis driven by autoreactive CD4+ T cells that is followed by progressive fibrosis, cardiomyopathy and systolic dysfunction. Purpose: The aim of the study was to investigate the role of cardiac fibroblasts and myofibroblasts in myocarditis and post-inflammatory dilated cardiomyopathy in mouse model of EAM. Methods: EAM was induced in BALB/c mice by immunization with αMyHC/CFA. We used reporter mice expressing EGFP under collagen type I promoter (Coll-EGFP) and RFP under a control of α-smooth muscle actin (αSMA) promoter (αSMA-RFP) and transgenic αSMA-TK mice with ganciclovir-inducible ablation of proliferating myofibroblasts. Cardiac cells were quantified using flow cytometry. Cardiac fibroblasts (CD45-CD31-EGFP+) were sorted from healthy and myocarditis-positive (day 21) mice using BD FACSAria™ II Cell Sorter and analyzed for the whole genome transcriptomics by RNA sequencing. Echocardiography was performed on Vevo 2100 Imaging System. Cardiac fibrosis was assessed by Trichrome Massons's staining and hydroxyproline assay, whereas cardiac hypertrophy by analysing cross-sectional cardiomyocyte area. Profibrotic gene expression was assessed by qRT-PCR. Results: The total number of cardiac fibroblasts (CD45-CD31-EGFP+) and the subset of myofibroblasts (CD45-CD31-EGFP+RFP+) remained unchanged at inflammatory (d21) and fibrotic stages (d40). Analysis of differentially expressed genes (min. 2x fold change, p value <0.05) pointed out activation of immune processes (mainly chemokine production), response to stress, cytoskeletal and extracellular matrix re-organization in cardiac fibroblasts in response to myocarditis. αSMA-TK mice treated with ganciclovir (from day 21) showed comparable percent of fibrotic area, but significantly reduced heart weight, decreased cardiomyocyte hypertrophy and improved ejection fraction and cardiac output at day 40 comparing to PBS-treated mice. Ganciclovir-treated mice showed also attenuated cardiac Acta2 and Srf but markedly enhanced Mmp2 expression. Conclusions: In EAM model cardiac fibroblasts actively participate in proinflammatory and profibrotic responses, while activated myofibroblasts contribute to dilated cardiomyopathy development independently of cardiac fibrosis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre (Poland)